Historical Literature (Íslendingabók, Landnámabók) (Oxford University Press, 2022)
In the early 12th century, two major texts on the early history of the Icelanders were composed. One of them is the relatively brief Íslendingabók (Book of Icelanders), composed by the priest and chieftain Ari Þorgilsson (b. c. 1067–d. 1148) between 1122 and 1133. In the prologue, Ari relates that he showed an early draft to the two bishops of Iceland, Þorlákr Runólfsson (b. 1086–d. 1133) and Ketill Þorsteinsson (b. 1075–d. 1145), and another priest and chieftain, Sæmundr Sigfússon (b. 1056–d. 1133). This early version has not been preserved. Ari uses very few written sources, mostly concerning events outside of Iceland, but he mentions nine oral informants. Íslendingabók has been preserved in a 17th-century manuscript, based on an original written around 1200. It is believed that an early version of Landnámabók (Book of settlements) was also composed in the early 12th century. Very little is known about this version except the names of two major contributors, the aforementioned Ari Þorgilsson and Kolskeggr Ásbjarnarson. In the early 13th century, another lost version of Landnámabók was made, by the prior Styrmir Kárason (d. 1245) of the canonry at Viðey. The earliest preserved versions of Landnámabók were composed by the lawman Sturla Þórðarson (b. 1214–d. 1284), the lawman Haukr Erlendsson (b. c. 1264–d. 1334), and someone of the family at Melar, most likely the lawman Snorri Markússon (d. 1313). In a prologue to his version, probably composed between 1306 and 1308, Haukr Erlendsson mentions earlier, lost versions of Landnámabók, and the prologue to his version, Hauksbók, is the chief source as to the development of that text. Sturlubók and Hauksbók are voluminous texts, whereas only fragments have been preserved of Melabók. There are two 17th-century versions of Landnámabók which are of importance. One, called Skarðsárbók, was composed by the priest Björn Jónsson (b. 1574–d. 1655) and is a conglomeration of Sturlubók and Hauksbók. The other, composed by the priest Þórðr Jónsson (b. 1609–d. 1670), is based on Skarðsárbók and Melabók, and provides some insight into some of the material that was in the lost parts of Melabók. Thus, there are three medieval and two early modern versions of Landnámabók that are of importance for the study of the text, but the original version (if there was only one) has not been preserved.